Effect of Erbium, Chromium-doped: Yttrium, Scandium, Gallium and Garnet Laser Tooth Preparation on Gap Formation of Universal Adhesive Bonded to Enamel and Dentin: A Micro-CT and SEM Study: Effect of Er, Cr: YSGG Laser Tooth Preparation on Gap Formation - AlQussier, Anfal; Awliya, Wedad (Journal of Lasers in Medical Sciences, 2022)
Introduction: The presence of gaps at the bonding interface of resin composite restorations is known to have an impact on restoration longevity. This study aimed to evaluate the effect of erbium, chromium-doped yttrium, scandium, gallium, and garnet (Er, Cr:YSGG) laser irradiation on gap formation at the tooth–resin interface and to compare the reliability of micro-computed tomography (µCT) and scanning electron microscopy (SEM) scans for gap formation assessment. Methods: Thirty standardized non-retentive class V cavities were prepared on sound human premolars using either an Er,Cr:YSGG laser or a round carbide bur (n=15 for each). A universal adhesive and A nano-filled resin composite were applied in accordance with the manufacturer’s recommendations. After water storage for 24 hours at 37°C, the teeth were subjected to thermocycling. Gap formation assessments were performed by µCT (Skyscan 1173 µCT, Brucker, Belgium) and SEM (JEOL JSM6610LV, Japan), and SPSS version 24.0 (IBM Inc., Chicago, USA) was used to analyze the data at P value<0.05. Descriptive statistics were used to describe the gap formation percentages. To compare the impact of both preparation and assessment methods, a non-parametric Mann–Whitney U test was used. Results: In enamel, similar gap formation values were detected for the two preparation methods (bur and laser). However, the laser-prepared group showed higher gap formation values in dentin. Additionally, higher gap formation values were reported for both preparation methods when µCT was used for assessment. Conclusion: Cavity preparation using a Waterlase laser led to higher gap formation percentages at the dentin–resin interface. In addition, SEM assessment is more reliable for assessing the tooth–resin interface. Doi:10.34172/jlms.2022.14.